2016
DOI: 10.1007/s00424-016-1882-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multiphoton imaging of immune cell dynamics

Abstract: Multiphoton imaging has been utilized to analyze in vivo immune cell dynamics over the last 15 years. Particularly, it has deepened the understanding of how immune responses are organized by immune cell migration and interactions. In this review, we first describe the following technical advances in recent imaging studies that contributed to the new findings on the regulation of immune responses and inflammation. Improved multicolor imaging of immune cell behavior has revealed that their interactions are spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…A major limitation to interrogating such mechanisms in mice has been the inability to couple comprehensive analyses of tumors early during treatment (e.g., when the tumors are still comparable in size between groups) with the ultimate disease outcome later following treatment. While some methods like intravital microscopy (IVM) have been useful for tracking longitudinal antitumor responses in some settings, IVM has a number of limitations that preclude its ability to be widely used for biomarker studies (42,52). Here we utilized a model of resection and response evaluation to investigate the responsiveness of breast tumors to anti-PD-1 blockade using a bilateral tumor approach in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation to interrogating such mechanisms in mice has been the inability to couple comprehensive analyses of tumors early during treatment (e.g., when the tumors are still comparable in size between groups) with the ultimate disease outcome later following treatment. While some methods like intravital microscopy (IVM) have been useful for tracking longitudinal antitumor responses in some settings, IVM has a number of limitations that preclude its ability to be widely used for biomarker studies (42,52). Here we utilized a model of resection and response evaluation to investigate the responsiveness of breast tumors to anti-PD-1 blockade using a bilateral tumor approach in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system consists of a variety of cell types. By using cell-specific fluorescent labelling with antibodies conjugated with chemical dyes or transgenic techniques, individual cell dynamics have been visualized in the mouse body with multiphoton excitation microscopes [49]. In FRET-TG mice, neutrophils could be easily distinguished by the segmented nuclei from lymphocytes or macrophages [44].…”
Section: Erk Activities In Cell Migration In Vivomentioning
confidence: 99%
“… 19 , 20 IVM studies have revealed critical insights into the pathogenesis of HIV, 21 influenza, 22 and West Nile, 23 among other viruses, 24 , 25 and the host’s immune response to virus infections. 26 Being increasingly accessible to modern day biomedical laboratories, IVM represents a powerful tool for understanding how viruses naturally infect host cells and are cleared by, or evade, the host’s immune system.…”
Section: Introductionmentioning
confidence: 99%